Análisis de conceptos administrativos para las MIPYMES dedicadas a la oferta del turismo de aventura en la ciudad de Armenia (2016)
This research aims to make the analysis of administrative concepts: planning, human talent, innovation, environment, market, strategies and finances in the current state of MSMEs dedicated to offer adventure tourism in the city of Armenia, this due the impact of tourism in the economic growth of Quindío in recent years and likewise contribute to the improvement of these companies offering adventure tourism and thus make a significant contribution to the sector of factual information.